2012
DOI: 10.1002/ppap.201100196
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‐enhanced Chemical Vapor Deposition of Aluminum Oxide Using Ultrashort Precursor Injection Pulses

Abstract: An alternative plasma‐enhanced chemical vapor deposition (PECVD) method is developed and applied for the deposition of high‐quality aluminum oxide (AlOx) films. The PECVD method combines a continuous plasma with ultrashort precursor injection pulses. We demonstrate that the modulation of the precursor flow in the reactor leads to enhanced control over plasma‐surface interactions. By variation of the time interval between the sequential Al(CH3)3 precursor injection pulses (10–50 ms) into the O2 plasma, the depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Passivation quality comparable to that of ALD can be achieved in PECVD AlO x films. Miyajima et al reported moderate passivation using this technique, but it was Dingemans et al who demonstrated efficient passivation with S eff of 0.45 cm s −1 in 3.5 Ωcm n‐type Si. In both cases they used a static reactor designed for laboratory research with a deposition rate of ∼5–10 nm min −1 .…”
Section: Materials and Methods For Silicon Surface Passivationmentioning
confidence: 98%
See 1 more Smart Citation
“…Passivation quality comparable to that of ALD can be achieved in PECVD AlO x films. Miyajima et al reported moderate passivation using this technique, but it was Dingemans et al who demonstrated efficient passivation with S eff of 0.45 cm s −1 in 3.5 Ωcm n‐type Si. In both cases they used a static reactor designed for laboratory research with a deposition rate of ∼5–10 nm min −1 .…”
Section: Materials and Methods For Silicon Surface Passivationmentioning
confidence: 98%
“…The seminal work of Agostinelli and Hoex was rapidly expanded. Most notably, the studies of Benick and Richter , Dingemans et al and Saint‐Cast et al , largely advanced the understanding of the electrical properties of the film, its passivation effectiveness, and its application to silicon solar cells. A key aspect of the passivation achieved using AlO x is the requirement for an activation step.…”
Section: Materials and Methods For Silicon Surface Passivationmentioning
confidence: 99%
“…124 A difference may be the refractive index of the PECVD deposited films, which is generally somewhat lower ($1.60) than for ALD ($1.64). 124,125 This is indicative of a slightly lower film density.…”
Section: Ald or Pecvd?mentioning
confidence: 99%
“…In addition to the continuous flow processes, an alternative PECVD process has been reported in which the Al(CH 3 ) 3 precursor was pulsed. 98,125 This pulsed process leads to additional control over the material properties. Collectively, the various reports have shown that for optimized PECVD processes the passivation quality of the deposited aluminum oxide films can be quite comparable to that achieved by ALD.…”
Section: Pecvdmentioning
confidence: 99%
“…From previous studies on thin film deposition by low pressure PE‐CVD, it is known that, in the absence of ion bombardment, the microstructure of thin films can be modified by chemical interaction of plasma radicals with the film surface or by irradiation with high energy photons generated by the plasma. By pulsing the injection of metal precursors in a continuous plasma, the film growth can be alternated with exposures to highly reactive plasma species which induce a densification of the film . Plasma‐generated, near‐UV luminescence can modify the defect structure in the film lattice or enhance the kinetics of surface reactions during the growth, thus affecting the structural and electrical properties of the film .…”
Section: Atmospheric Pe‐cvdmentioning
confidence: 99%